(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
For establishment of identity from human remains, it is customary to start with Sex, Age, Stature and Race at the time of death known as the “Big Four”. Sex is the key components of partial identification. They provide one important aspect of an individual’s physiognomy1. Dimensions of various parts of the body shows sexual dimorphism also. Dimensional relationship between body segments and sex has been the focus of scientists for many years. Various studies have been conducted all over the world for establishment of identity by means of sex from various body parts like hand, feet, fingersear etc. Prediction of sex from cranial remains is vital in establishing the identity of an unknown individual hence cranial parts such as face and nose have been used in studies for determination of sex by forming indices. Therefore the present study was carried out to evaluate sexual dimorphism in nasal index calculated from nasal dimensions in cadavers brought for the post-mortem examination at mortuary of P. D. U. Govt. Medical College and Hospital, Rajkot for population in and around Rajkot region of Gujarat.Total 100 male cases and 100 female cases randomly selected from cadavers brought for post mortem examination at mortuary of P. D. U. Govt. Medical College and Hospital, Rajkot. Nasal dimensions were measured by Spreading caliper after breaking Rigor mortis, if developed.Collected data were statistically analysed using software like Epi info 7 and Microsoft excel.Demarking points, Discriminant function equations and their sectioning points were derived to determine sex from Nasal Height, Nasal Breadth and Nasal Index. Value more than demarking point and sectioning points suggests male and value less than demarking point suggests female.